Repurposing FDA-Approved Drugs as Fructosamine-3-Kinase Inhibitors: A Mechanistic and Translational Approach to Redox-Driven Cancer Therapy - Alves, Erica; Bannimath, Gurupadayya; Prabhakaran, Prabitha (Drug Research, 2025)
Fructosamine-3-kinase (FN3K), a deglycating enzyme originally studied in the context of diabetes, has recently emerged as a pivotal modulator of redox homeostasis and therapeutic resistance in cancer. FN3K catalyzes the removal of early glycation adducts, thereby stabilizing redox-sensitive proteins such as Nuclear factor erythroid 2–related factor 2 (Nrf2), a key transcriptional regulator of antioxidant defense. This review explores the evolving role of FN3K in tumor metabolism, highlighting its expression patterns across cancer types, structural features amenable to therapeutic targeting, and mechanistic interplay with the Nrf2 pathway. Emphasis is placed on FDA-approved drugs with FN3K-modulatory potential, evaluated through computational modeling, docking simulations, and structure – activity insights. The analysis reveals a dual opportunity: to repurpose redox-active agents as FN3K inhibitors and to exploit FN3K as a biomarker for redox stratification in precision oncology. Despite promising in silico data and preclinical correlations, challenges remain – particularly in achieving target selectivity, overcoming structural limitations, and validating pharmacodynamic markers. Addressing these barriers through integrated translational strategies could unlock FN3K as a tractable node in redox-driven cancer therapy.
Keywords: fructosamine-3-kinase (FN3K); redox homeostasis; Nrf2 signaling; cancer metabolism; drug repurposing; deglycation; computational modeling; precision oncology